Implementation Plan in Response to the Executive Board-Endorsed Recommendations for the IEO Evaluation Report : The IMF and the Crises in Greece, Ireland, and Portugal. (Policy Papers; Policy Paper ;, 2017)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) report The IMF and the Crises in Greece, Ireland, and Portugal as part of the Management and staff follow-up to an IEO evaluation. The implementation plan proposes specific actions to address the recommendations endorsed by the Executive Board in its July 19, 2016 discussion. The implementation plan notes the Board's endorsement of the principles that the IMF's technical analysis should remain independent, that existing policies should be followed and should not be changed without careful deliberation, and that the Executive Board and Management should reaffirm their commitment to accountability and transparency, as well as the role of independent evaluation in fostering good governance. As to the IEO's specific recommendations supported by the Board, the implementation plan proposes actions to address the need for the Fund to clarify how guidelines on program design apply to currency union members, the need for the Fund to establish a policy on cooperation with regional financing arrangements, and the need to further strengthen Fund cooperation with the IEO, including on modalities of interactions between the IEO and Fund staff and the IEO's access to information. The implementation of some of the proposed actions is already underway and some actions have been included in the Fall 2016 Work Program. The paper also explains how implementation will be monitored by the Executive Board.